The sustainable development goals and the University of Bath: An opportunity - Nichole M. Schantz; Aurelie Charles; James G. Copestake (University of Bath, Centre for Development Studies (CDS), 2021)
The United Nations (UN) has designated the 2020s as the 'decade of action' to meet the Sustainable Development Goals (SDGs). This paper responds to the call for universities to join this effort by reviewing how the University of Bath could support the SDGs more fully. A first step is monitor alignment of teaching and research with the 17 SDG goals. Having reviewed how to do this, we then review their role in relation to university management and stakeholder engagement, considering in turn how this can be linked with action on climate change, local collaboration and civic partnerships, engagement with the business sector, international networking, and the role of the SDGs in University league tables and rankings. We conclude with eight recommendations. These cover steps to strengthen a sense of shared purpose among staff and students, increase public awareness of what the University does, and facilitate cross-disciplinary research collaboration and innovative teaching. Universities can choose how far to align themselves with the SDGs over the next decade, but not how far the SDGs will be used by others to evaluate them.
Keywords: 330; Sustainable Development Goals; universities; climate change; higher education; league tables